2023
DOI: 10.3390/coatings13061097
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Fenton-like Catalyzation of Nanoscale Schwertmannite for Sulfamethoxazole Degradation

Abstract: Sulfamethoxazole (SMX) contamination in large quantities of wastewater can cause potential environmental problems. Due to difficulty in degrading SMX by natural processes, it is necessary to develop a novel technology to solve this problem. Advanced oxidation processes (AOPs) have been identified as methods with a high potential to treat recalcitrant organic pollutants. The nanoscale schwertmannite (nano-SWT) was prepared with an indoor-temperature synthesis method facilitated by polyvinylpyrrolidone (PVP). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…Additionally, Liu et al (2022) found that Sedum plumbizincicola nanoparticles can effectively remove Bisphenol A (BPA) from complex wastewater, demonstrating stable and efficient reactions [29]. Nanoscale schwertmannite (nano-SWT) was prepared using an indoor temperature synthesis method with the assistance of polyvinylpyrrolidone, and nano-SWT was found to be effective in reducing sulfamethoxazole in the presence of Fenton-like catalysts using hydrogen peroxide (H 2 O 2 ) [30]. Currently, Fenton catalysts are widely employed in conjunction with nanoparticles for environmental contaminant removal.…”
mentioning
confidence: 99%
“…Additionally, Liu et al (2022) found that Sedum plumbizincicola nanoparticles can effectively remove Bisphenol A (BPA) from complex wastewater, demonstrating stable and efficient reactions [29]. Nanoscale schwertmannite (nano-SWT) was prepared using an indoor temperature synthesis method with the assistance of polyvinylpyrrolidone, and nano-SWT was found to be effective in reducing sulfamethoxazole in the presence of Fenton-like catalysts using hydrogen peroxide (H 2 O 2 ) [30]. Currently, Fenton catalysts are widely employed in conjunction with nanoparticles for environmental contaminant removal.…”
mentioning
confidence: 99%